2007
DOI: 10.1021/jp073912x
|View full text |Cite
|
Sign up to set email alerts
|

Eigen and Zundel Forms of Small Protonated Water Clusters:  Structures and Infrared Spectra

Abstract: The spectral properties of protonated water clusters, especially the difference between Eigen (H3O+) and Zundel (H5O2+) conformers and the difference between their unhydrated and dominant hydrated forms are investigated with the first principles molecular dynamics simulations as well as with the high level ab initio calculations. The vibrational modes of the excess proton in H3O+ are sensitive to the hydration, while those in H5O2+ are sensitive to the messenger atom such as Ar (which was assumed to be weakly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
143
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(168 citation statements)
references
References 63 publications
22
143
0
3
Order By: Relevance
“…[25][26][27] We note that the other fundamental vibrations found by AIMD in the fingerprint region as assigned by MCTDH show similar character. [9,31,33,34] However, tagging effects are found to be dramatic for the 1000 cm À1 proton-transfer mode (Figure 2 d).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…[25][26][27] We note that the other fundamental vibrations found by AIMD in the fingerprint region as assigned by MCTDH show similar character. [9,31,33,34] However, tagging effects are found to be dramatic for the 1000 cm À1 proton-transfer mode (Figure 2 d).…”
supporting
confidence: 64%
“…[16] It should be noted that AIMD simulations of the Ar-tagged complex also yield only two IR absorption peaks in the O-H stretch region. [26] Thus, also for the Ar-tagged Zundel complex, our findings predict a similar mixture of tightly and weakly bound adducts, whereas the Ne-tag apparently does not noticeably perturb the bare Zundel ion spectrum. [16] Similar effects are observed for the doublet structure at about 1000 cm À1 (Figure 2 e), which has been assigned by MCTDH for the bare Zundel ion to a Fermi resonance of the proton-transfer fundamental and a combination of lower frequency modes [9] (see Figure 2 e and 2 a).…”
supporting
confidence: 60%
“…Extensive experimental [24][25][26][27][28] and theoretical [29][30][31][32][33][34][35][36][37] studies of an isolated Zundel cation in the gas phase have been conducted, most notably by means of vibrational spectroscopy [38,39], to probe its structure and the extent of the coupling between its constituent atoms. In both experimental and computational studies, the H/D isotopic substitution were found to significantly affect the intensity of infrared peaks of mixed H/D species [40,41].…”
Section: Together With the Eigen Cation H 3 Omentioning
confidence: 99%
“…[44] However, the AIMD results reveal a prominent temperature dependence for this spectral feature, [49,51] and hence it could be speculated that the temperature dependence of classical nuclear dynamics underlying such AIMD simulations may have hampered earlier studies [52][53][54][55] in reproducing (even qualitatively) the doublet feature. Studies on the influence of the messengers on the spectra additionally must deal with a sufficiently accurate description of the weak intermolecular interactions within the employed electronic structure method and, importantly, sufficient sampling of the vast phase space accessible to these floppy systems at finite temperature.…”
Section: Introductionmentioning
confidence: 94%
“…Studies on the influence of the messengers on the spectra additionally must deal with a sufficiently accurate description of the weak intermolecular interactions within the employed electronic structure method and, importantly, sufficient sampling of the vast phase space accessible to these floppy systems at finite temperature. [51,53,55] Here, attempts to resolve the effect of noble gas messengers such as Ne and Ar were hampered by the description of the delicate dispersive interactions of these atoms with the protonated water clusters. Whereas a typical correlation method such as MP2 should yield sufficiently accurate interaction forces, its computational effort makes it difficult to comprehensively sample the intricate large-amplitude dynamics of the adduct species.…”
Section: Introductionmentioning
confidence: 99%